Knowledge of Nigeria Wildlife Conservation Laws among Officials of Okomu and Old Oyo National Parks, Nigeria (2020)
One of the key resources in effective management of National Parks is the knowledge base of the park managers. There is however little or no documented information about park official’s knowledge of the laws they uphold in Nigeria. This study assessed the knowledge base of Nigeria wildlife laws among park officials in Okomu National Park (ONP) and Old Oyo National Park (OONP), Nigeria. Simple random sampling was used to administer structured questionnaire to 50 ONP and 130 OONP staff. Data were analysed using descriptive statistics. Majority (95.6%) had heard about wildlife laws and 68.9% understood the contents of the law. Majority (72.2%) knew the decree responsible for the establishment of national parks but could not distinctively identify the activities that constitute offences under this law. For effective park management, proper orientation, education, training and re-training on the wildlife laws should be organized for the park officials at regular intervals.